The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.2174/1874357901711010028
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Melanoma with Cancer-Killing Viruses

Abstract: Melanoma is the deadliest skin cancer with ever-increasing incidence. Despite the development in diagnostics and therapies, metastatic melanoma is still associated with significant morbidity and mortality. Oncolytic viruses (OVs) represent a class of novel therapeutic agents for cancer by possessing two closely related properties for tumor reduction: virus-induced lysis of tumor cells and induction of host anti-tumor immune responses. A variety of viruses, either in “natural” or in genetically modified forms, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 166 publications
0
5
0
Order By: Relevance
“…Results showed that in melanoma cells that carried V600D or V600E BRAF mutations there had been an increased apoptosis [ 42 ]. Also, the combination of reovirus and radiation has shown to increase the tumor growth delay of the melanoma xenografts in the treated animals, and significantly improve the overall survival rate compared to the treatment with either of the individual therapies [ 118 ]. Importantly, Ras mutation is one of the driver mutations for melanoma and is associated with radio-resistance [ 58 ].…”
Section: Combinatorial Approaches With Ovs In Melanoma Treatmentsmentioning
confidence: 99%
“…Results showed that in melanoma cells that carried V600D or V600E BRAF mutations there had been an increased apoptosis [ 42 ]. Also, the combination of reovirus and radiation has shown to increase the tumor growth delay of the melanoma xenografts in the treated animals, and significantly improve the overall survival rate compared to the treatment with either of the individual therapies [ 118 ]. Importantly, Ras mutation is one of the driver mutations for melanoma and is associated with radio-resistance [ 58 ].…”
Section: Combinatorial Approaches With Ovs In Melanoma Treatmentsmentioning
confidence: 99%
“…Furthermore, a novel oHSV Ld0-GFP (which was derived from the oncolytic ICP0-null HSV) targeting hepatocellular carcinoma (HCC) has recently been reported [12]. In 2016, the oHSV T-VEC has been approved for the treatment of melanoma [13,14].…”
Section: Ivyspringmentioning
confidence: 99%
“…Oncolytic virotherapy uses replication-competent viruses that can selectively replicate and kill cancer cells [ 11 , 12 , 13 , 14 , 15 , 16 ]. Oncolytic viruses (OVs) lead to cancer cell death through different mechanisms including apoptosis, pyroptosis, and necroptosis.…”
Section: Introductionmentioning
confidence: 99%